The Concept of Children’s Education from The Qur'an Perspect - Ridwan, Ahmad; Pasaribu, Selamat; Drajat, Amroeni; Salminawati, Salminawati (Jurnal Basicedu, 2022)
This study aims to analyze the concept of children's education in the perspective of the Koran. In this context, the essence of the meaning of the term tarbiyah becomes the basic foundation of research. This research uses a qualitative approach with a literature study method. Data collection and analysis was carried out using scientific reference materials, including scientific articles, books, proceedings and final assignments (thesis, theses, dissertations) which were tracked via the internet on the google scholar indexer, DOAJ, science direct, and scimago JR. The results of this study found that the concept of child education in the Qur'an contains an element of "love" like parental education for children in the concept of tarbiyah. The elements of the concept of education for children in the perspective of the Qur'an describe learning obligations, educational goals, the role of educators, educational objects, educational methods, and educational materials for children. Thus, the education given to children is comprehensively based on the worldview of monotheism in realizing human beings (perfect).